The Impact of EU Liberalization Regulations on the Market Audiovisual Media Services Market - Péter Bordás (Studia Iuridica Lublinensia, 2022)
In the last years, the audiovisual media services market has changed significantly from its initial stage of liberalization. Of course, if we look at the steps as far as the regulation of services is concerned, it has also undergone significant changes, but the assessment of the effectiveness of liberalization may be different. This is simply because with the development of technology, such as the emergence of online services, various new sorts of services and players have entered the market, the regulation of which requires EU action in several respects. Firstly, the significance of this lies in the fact that, in order to achieve media convergence, the scope of regulation has now expanded compared to the early stage of liberalization. Secondly, large service providers outside of Europe are now competing for European consumers, that poses a challenge to both the regulation and the interests of the EU. Thirdly, it has to be mentioned that the Brexit, occurred in early 2020, re-arranged the map of the European audiovisual services market and relocated several service providers to an EU Member State. This study – in order to understand the phenomena outlined above – seeks to analyse the liberalization of a small slice of the European telecommunications market.